Refinement of the crystal structure of β-3,4:9,10-perylenetetracarboxylic dianhydride, C24H8O6, at 223 K - Tojo K. (Zeitschrift für Kristallographie - New Crystal Structures, 2002)
C24H8O6, monoclinic, P121/c1 (No. 14), a = 3.74(7) Å, b = 18.95(8)Å, c = 10.75(9)Å, β = 96(1)°, V = 757.7 Å3, Z = 2, Rgt(F) = 0.046, wRref(F2) = 0.138, T = 223 K.